Peningkatan Kapasitas Pendamping UMKM dalam Menjaga Kerahasiaan Data Pribadi Klien pada Komunitas Aurum First Sunrise di Surakarta Jawa Tengah - Wahyudi, Eko Nur; Handoko, Widiyanto Tri; Lestariningsih, Endang (Pusat Riset dan Inovasi Nasional, 2026)
This community service activity aimed to enhance the security and efficiency of halal certification mentoring services at the Aurum First Sunrise community in Surakarta. The main challenge faced by the partner was the risk of sensitive SME data leakage such as ID cards, recipes, and supply chain information, due to the lack of an adequate document security mechanism. The core solution implemented was Technology Implementation in the form of a Cryptographically-based Document Management Information sistem (utilizing the Light Weight PDAC algorithm) integrated with digital access rights management and user Training. Evaluation demonstrated successful implementation, evidenced by an increase in the average satisfaction of SMEs regarding data security to 97.8%, confirming enhanced trust. Furthermore, digitalization successfully improved the efficiency of the mentoring team, reflected by a satisfaction score of 85.0%. In conclusion, this service successfully transformed the partner into a secure, efficient, and credible mentoring institution, significantly supporting SMEs in accessing halal certification.